The Importance of Enrichment in Wildlife Rehabilitation (Part One) - Gulas–Wroblewski, Bonnie E. (Wildlife Rehabilitation Bulletin, 2007)
Enrichment is extremely important to the welfare of animals, both those in the process of rehabilitation and permanent members of a facility. Enrichment is essential for maintenance of mental and physical well being of animals. Research has shown that active enrichment programs reduce stress and aberrant behaviors in captive animals, which benefits not only a facility’s permanent residents, but in turn can promote faster healing of injured and sick patients and aid in reintroduction to the wild. Enrichment can promote natural behaviors that help acclimate rehabilitated and orphaned animals to the wild. For captive animals, enrichment can reduce stress and increase physical activity.